State of the art and challenges in development of electrical contact materials in the light of the RoHS directive - Ćosović V.; Ćosović A.; Talijan N.; Živković D.; Živković Ž. (Science of Sintering, 2012)
The article surveys current state of the art and challenges in the development of the electrical contact materials in the light of the EU Directive on Restriction of Hazardous Substances (RoHS). The focus was placed on widely used silver-cadmium alloys. According to this directive, as of July 1, 2006, use of six hazardous materials, including cadmium, are restricted for applicable electrical and electronic products intended for the EU market. In contrast, traditionally preferred material for production of electrical contacts is Ag-CdO, due to its outstanding functional properties. These conflicting interests result in present state where RoHS directive has not yet been implemented in its original form and has undergone numerous amendments and exceptions regarding the use of cadmium. Main reason for this seems to be the unrealistic time frame imposed by legislation. Although, significant effort has been put into research and development of alternative materials, there are still cases where adequate replacement materials had not been found. Therefore, importance of synchronicity between legislation and technological progress i.e. communication between legislative administration and industry and academia is brought to light as well as some common issues that may arise with an introduction of new replacement materials or product modification. [Projekat Ministarstva nauke Republike SRbije, br. OI 172037 and TR 34023]